High-technology surgical methods in the comprehensive medical rehabilitation of patients with rheumatic diseases and joint pathology of the upper and lower extremities - Vadim Petrovich Pavlov; S A Makarov; M A Makarov; A L Logunov; Ya B Khrennikov; V V Kolomatsky; M M Lipina; A A Roskidailo; D V Ivanov (Современная ревматология)
A large clinical material (1693 patients with rheumatic diseases — RD, 2066 operations) was used to develop a three-level medical rehabilitation system using differentiated, including high-technology surgical methods depending on the nosology, RD stage, localization of joint diseases of the upper and lower extremities during adequate drug therapy. A positive result persisting for 1 to 20 years was achieved in 60—92% of cases.